Study of Ontological, Epistemological and Axiological Principles in Final Academic Assignments for Dissertation Scientific Papers: Philosophical Values in Scientific Writing - Manik, Kresna Ningsih; Nababan, Irene Ardyani; Sai, Yong Heng; Ginting, Siti Aisha; Sari, Winda (Future Science / FSH-PH Publications, 2024)
This research is an initial exploration into the foundational branches of philosophy (axiology, ontology, and epistemology) and their profound implications for the philosophy of language. Investigating the contemporary study of language, the research examines five dissertations to uncover the interplay of these three philosophical domains. The research addresses three key questions: the domains within the philosophy of language covered by the dissertations, the featured interconnection of axiology, ontology, and epistemology in these dissertations, and the development of these domains to bolster arguments. The objectives include discerning how researchers describe these domains in relation to language philosophy, exploring the possibility of discussing a single domain without engaging the others, and fostering an objective discussion of language philosophy within an academic context. The research's significance lies in contributing to a comprehensive understanding of language, its relationship with users and the world, and how the three philosophical domains sustain language existence. It aims to enrich the study of language philosophy for students, particularly those in English Applied Linguistics programs, by emphasizing the correlations between philosophy and language characteristics, acquisition, planning, and translation. The research employs a qualitative approach, analyzing dissertations from a philosophical perspective. Findings reveal that the interconnection of axiology, ontology, and epistemology is intricate, challenging the initial assumption of discussing them separately. Notably, the dissertations exhibit varied emphasis on the three domains. The study concludes with valuable insights into the philosophy of language, highlighting the pivotal role of language in shaping reality, conveying experiences, and expressing cultural influences. The dynamic nature of language and the reciprocal relationship between language and philosophy underscore the need for an open-minded approach and continual engagement in discussions surrounding language philosophy. The research recommends incorporating philosophy as a mandatory course in university curricula to nurture a holistic understanding of language and its philosophical underpinnings.